Hypoglycaemia, cardiovascular disease, and mortality in diabetes: epidemiology, pathogenesis, and management. Issue 5 (May 2019) - ,; Amiel, Stephanie A; Aschner, Pablo; Childs, Belinda; Cryer, Philip E; de Galan, Bastiaan E; Frier, Brian M; Gonder-Frederick, Linda; Heller, Simon R; Jones, Timothy; Khunti, Kamlesh; Leiter, Lawrence A; et al.
Summary: Hypoglycaemia has long been recognised as a dangerous side-effect of treatment of diabetes with insulin or insulin secretagogues. With its potential to disrupt cerebral function, hypoglycaemia can have a major effect on peoples' lives. Study findings have suggested that hypoglycaemia is associated with an increased risk of cardiovascular events and mortality. Different mechanisms by which hypoglycaemia might provoke cardiovascular events have been identified in experimental studies, and in clinical studies cardiac arrhythmias have been reported to be induced by hypoglycaemia, with one report describing sudden death during a severe episode. Emerging evidence suggests that the association between hypoglycaemia and cardiovascular events and mortality is likely to be multifactorial. The association is probably partly caused by confounding, with hypoglycaemia occurring more frequently in people with comorbidities who are also more likely to die than those without. However, people with type 1 or type 2 diabetes also seem at risk of hypoglycaemia-induced cardiovascular effects. This risk should be recognised by clinicians when agreeing glycaemic goals with patients and choosing appropriate glucose-lowering therapies.